Pendampingan Penerapan Digitalisasi Operasional Bisnis Pada SP Alumunium - Andri, Bryan Shafryzal; Sumaryanto, Sumaryanto (Jurnal Dharma Bhakti Ekuitas, 2023)
Community service aims to analyze and educate about the digitalization of business operations SP Alumunium, which can provide benefits in information management and reporting using Google features. SP Aluminum is a large company, but its production operations have not been fully digitalized. The use of Google features is the focus of digitalization for IKM SP Alumunium related to production and financial reporting. Google, which can be accessed by everyone, can be an efficient information exchange medium for SP Alumunium. The program is carried out in several stages, starting with the planning stage, which involves research on educating the production manager about using spreadsheets for reporting to the admin department. The second stage is implementation, which involves observing and interviewing the production admin of SP Alumunium about the components used in the reporting of each polishing and turning process in production. Finally, there is the evaluation stage, which involves assessing the partner's understanding of operating digital-based financial reports. The results of the community service include the creation of spreadsheets, a list of employee bonus determinations, and a flow diagram of the polishing production process, which can be a reference for the beneficiaries. The digitalization of business operations at IKM SP Alumunium provides an integrated reporting medium using spreadsheets. This reporting medium can be freely used by SP Alumunium to report production results, determine wages and bonuses, and quickly access information at the central office. The spreadsheets produced can facilitate access to information for the central office of SP Alumunium for production determination. The ease of use and development of spreadsheets is expected to encourage the aluminum industry sector to develop its reports following technological advancements. Keywords: Digitalization, Business Operations, spreadsheet. Abstrak Pengabdian kepada masyarakat bertujuan untuk menganalisis dan mengedukasi mengenai digitalisasi operasional bisnis pada SP Alumunium yang dapat memberikan manfaat pengelolaan informasi dan pelaporan menggunakan fitur google. SP Alumunium merupakan perusahaan dalam tahapan yang besar namun belum didukung dengan operasional yang terdigitalisasi pada bagian produksi. Penggunaan fitur google menjadi fokus digitalisasi pada IKM SP Alumunium terkait laporan produksi hingga keuangan. Google yang dapat diakses semua orang dapat menjadi media pertukaran informasi yang efisien bagi SP Alumunium. Dalam pelaksanaan program ini dilakukan dengan beberapa tahapan yaitu tahap perencanaan dilaksanakan dengan melakukan riset terkait edukasi penggunaan spreadsheet sebagai pelaporan kepala produksi kepada bagian admin. Tahap kedua adalah pelaksanaan yang dilakukan dengan observasi dan wawancara pada Admin produksi SP Alumunium mengenai komponen apa saja yang digunakan dalam laporan setiap proses polish dan bubut di bagian produksi. Terakhir tahap evaluasi terhadap pemahaman mitra dalam mengoperasikan laporan keuangan berbasis digital. Hasil pengabdian adalah pembuatan spreadsheet, daftar penentuan bonus karyawan, dan diagram alur proses produksi polish dapat menjadi referensi bagi penerima manfaat. Hasil pelaksanaan pendampingan digitalisasi operasional bisnis pada IKM SP Alumunium memberikan media pelaporan terintegrasi menggunakan spreadsheet. Media pelaporan tersebut dengan leluasa digunakan oleh pihak SP Alumunium untuk melaporkan hasil bagian produksi, penentuan upah dan bonus, dan akses informasi yang cepat pada kantor pusat. Laporan spreadsheet yang dihasilkan dapat memudahkan akses informasi kantor pusat SP Alumunium untuk penentuan produksi. Kemudahan dan pengembangan spreadsheet diharapkan dapat mendorong sektor industri alumunium untuk mengembangan laporan yang ada mengikuti perkembangan teknologi.. Kata kunci: Digitalisasi, Operasional Bisnis, spreadsheet.